Nonlinear Imputation of PaO2/FIO2 From SpO2/FIO2 Among Mechanically Ventilated Patients in the ICU: A Prospective, Observational Study. Issue 8 (August 2017) - Brown, Samuel M.; Duggal, Abhijit; Hou, Peter C.; Tidswell, Mark; Khan, Akram; Exline, Matthew; Park, Pauline K.; Schoenfeld, David A.; Liu, Ming; Grissom, Colin K.; Moss, Marc; Rice, Todd W.; et al.
Abstract : Objectives: In the contemporary ICU, mechanically ventilated patients may not have arterial blood gas measurements available at relevant timepoints. Severity criteria often depend on arterial blood gas results. Retrospective studies suggest that nonlinear imputation of PaO2 /FIO2 from SpO2 /FIO2 is accurate, but this has not been established prospectively among mechanically ventilated ICU patients. The objective was to validate the superiority of nonlinear imputation of PaO2 /FIO2 among mechanically ventilated patients and understand what factors influence the accuracy of imputation. Design: Simultaneous SpO2, oximeter characteristics, receipt of vasopressors, and skin pigmentation were recorded at the time of a clinical arterial blood gas. Acute respiratory distress syndrome criteria were recorded. For each imputation method, we calculated both imputation error and the area under the curve for patients meeting criteria for acute respiratory distress syndrome (PaO2 /FIO2 ⩽ 300) and moderate-severe acute respiratory distress syndrome (PaO2 /FIO2 ⩽ 150). Setting: Nine hospitals within the Prevention and Early Treatment of Acute Lung Injury network. Patients: We prospectively enrolled 703 mechanically ventilated patients admitted to the emergency departments or ICUs of participating study hospitals. Interventions: None. Measurements and Main Results: We studied 1, 034 arterial blood gases from 703 patients; 650 arterial blood gases were associated with SpO2 less than or equal to 96%. Nonlinear imputation had consistently lower error than other techniques. Among all patients, nonlinear had a lower error ( p < 0.001) and higher ( p < 0.001) area under the curve (0.87; 95% CI, 0.85–0.90) for PaO2 /FIO2 less than or equal to 300 than linear/log-linear (0.80; 95% CI, 0.76–0.83) imputation. All imputation methods better identified moderate-severe acute respiratory distress syndrome (PaO2 /FIO2 ⩽ 150); nonlinear imputation remained superior ( p < 0.001). For PaO2 /FIO2 less than or equal to 150, the sensitivity and specificity for nonlinear imputation were 0.87 (95% CI, 0.83–0.90) and 0.91 (95% CI, 0.88–0.93), respectively. Skin pigmentation and receipt of vasopressors were not associated with imputation accuracy. Conclusions: In mechanically ventilated patients, nonlinear imputation of PaO2 /FIO2 from SpO2 /FIO2 seems accurate, especially for moderate-severe hypoxemia. Linear and log-linear imputations cannot be recommended. Abstract : Supplemental Digital Content is available in the text.